2020
DOI: 10.3390/f11010060
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of Nonindustrial Private Forest Owners’ Willingness to Harvest Timber in Norway

Abstract: In Norway, 84% of the productive forest is privately owned, and these forests dominate the supply of timber to industries. However, during last 80 years, annual forest growth has seen a substantial upsurge while annual timber harvest has been rather stable, generating an increasing potential for timber supply. In this study, we provide new insights to better understand Norwegian non-industrial private forest owners’ timber harvesting decisions. This was achieved by comparing the outcomes of two different stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Thus, FFOs' positive attitude towards extraction of more biomass from young dense stands is similar to their views on removal of logging residues after final-felling [23]. That the economic result of implementing whole-tree harvesting would affect the FFOs' attitude was expected since economic return is often found to be an important driver for performing forest management [24][25][26][27]. That only 6% would never consider undertaking whole-tree harvesting if it has an associated cost should thus be considered a positive sign for the future potential of this type of service.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, FFOs' positive attitude towards extraction of more biomass from young dense stands is similar to their views on removal of logging residues after final-felling [23]. That the economic result of implementing whole-tree harvesting would affect the FFOs' attitude was expected since economic return is often found to be an important driver for performing forest management [24][25][26][27]. That only 6% would never consider undertaking whole-tree harvesting if it has an associated cost should thus be considered a positive sign for the future potential of this type of service.…”
Section: Discussionmentioning
confidence: 96%
“…This model is centered on the utility theory or the rational choice perspective of behavior, which is based on the premise that people can systematically rank their choices based on their preferences [35]. Recent studies have used this approach to link decisions to the socioeconomic and productive characteristics of forest owners, see [36][37][38][39][40][41][42]. Although in this study the dependent variable does not represent an explicit decision, there is an implicit decision to extract forest products, whether they are wood or non-wood, which would negatively affect the success of the variable in the analysis.…”
Section: The Probit Modelmentioning
confidence: 99%
“…In fact, property size is one of the most frequently used variables in timber harvesting studies, and the majority of studies have confirmed the positive effect of property size on harvesting interest and intensity [21,55,64,67], and on response time [69]. However, Bashir et al [70] found that the forest size and timber harvest intensity are negatively correlated. In addition, forest size was inversely related to timber supply because of the higher productivity and larger growing stock recorded on smaller properties.…”
Section: + + +mentioning
confidence: 99%